Short‐term outcomes of single‐port surgery for palliative resection of the primary tumor in patients with incurable stage IV colon cancer. Issue 4 (26th April 2016) - Tei, Mitsuyoshi; Wakasugi, Masaki; Akamatsu, Hiroki
Abstract: Introduction: The aim of this study was to evaluate the short‐term outcomes of single‐port surgery (SPS) for palliative resection of the primary tumor in patients with incurable stage IV colon cancer. Methods: We studied 66 consecutive patients who underwent SPS or multiport surgery (MPS) for palliative resection of their primary tumor in our department from January 2008 to December 2013. Short‐term outcomes and the postoperative course were analyzed between groups retrospectively. Results: Of the 66 patients, 32 underwent SPS, and 34 underwent MPS. The groups did not differ significantly in terms of preoperative evaluation and short‐term outcomes. In the SPS group, one patient was converted to MPS (3.1%); no patients were converted to open surgery. Oncological resection, the proportion of patients who received postoperative chemotherapy, and time to the beginning of postoperative chemotherapy was similar in both groups. The 1‐year overall survival rates were 76.7% in the SPS group and 79.4% in the MPS group ( P  = 0.711). Conclusions: SPS is safe and feasible for palliative resection of the primary tumor in patients with incurable stage IV colon cancer.